Evaluation of prophylactic antibiotics to prevent early - onset clinical neonatal sepsis in newborn with potential infection. - T. Darmawati, T. Darmawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
Background: Over used prophylactic antibiotics on the potensially infected newborns to prevent early-onset sepsis causes greater risk for antibiotic resistance and changes of bacterial spectrum. Objectives: To know the efectiveness of prophylactic antibiotics to prevent early-onset clinical neonatal on the newborns with potential infection.Methods: Retrospective cohort study, neonates born in the Maternal Perinatal Installation of Dr. Sardjito General Hospital in Yogyakarta, from February 2000 to January 2001, were evaluated the risk factor of potential infection included premature rupture of the membranes, claudy or bad smell of amnion fluid, low birth weight, preterm, severe asphyxia with invasive procedure. Two groups in the study, were neonates with prophylactic antibiotics and neonates without prophylactic antibiotics. They were observed at least 7 days after delivery to find early-onset clinical neonatal sepsis.Results: There were 140 newborns studied, 50 newborns were given prophylactic antibiotics and 90 new borns without prophylactic antibiotics. Chi Square and t-test were applied for gestational age at delivery, peripartum 5 minutes. No significant difference between two groups (p>0.05) was found, early-onset neonatal sepsis in control group was 14/50 (28%) and in case group was 20/90 (22.2%)) = 0.445). Relative risk for sepsis was 0.79 (95% CI:0.303 - 0.078). Number needed to treat (NNT) was 18 (95% CI: 12 - 26) with risk of 72%.Conclusion: Prophylactic antibiotics for potensially infected newborn to prevent early-onset clinical neonatal sepsis did not result in significant different effect compared no prophylactic antibiotics.Keywords: no prophylactic antibiotics - early-onset neonatal sepsis - neonatal risk factors